EVALUASI PRAKTEK PERBANKAN SYARIAH DI INDONESIA : INTEREST RATE FREE? - Radia - Purbayati (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2019)
The aim of this study is to evaluate Islamic Banking practice truly interest rate free on determining funding and financing pricing. The object of this study are Islamic and Conventional Banking in Indonesia 2014-2018. Variables used in the study consists of equivalent rate (interest rate) of demand deposit, saving deposit, time deposit, working capital financing (loan) and financing (loan) in Islamic and Conventional Banking. VAR / VECM Modelling and Granger Causality Test applied on these 5 Models. The evidence shows that at that time there are only Model 2 and Model 5 were Granger Cause at one way in the short run. On the other hand, pricing on funding and financing product at islamic banking were determined by its time lag of pricing on funding and financing products at islamic and conventional banking , vice and versa. The shocks at the short run will be adjusted as its shocks response into long run equilibrium. It means the practicing Islamic banking in Indonesia is not truly interest rate free. Keywords : Pricing on funding and financing products, Islamic Banking, Conventional Banking, VAR/VECM Modelling, Granger Causality.